First Russian DPP-4 inhibitor Gosogliptin comparing to Vildagliptin in type 2 diabetes mellitus patients - Karina Oganesovna Galstyan (Endocrinology Research Centre, 2016)
Introduction.In the early 2000s, in type 2 diabetes mellitus (T2DM) treatment, a fundamentally new class of drugs appeared—the incretin mimetics. The use of dipeptidyl peptidase-4 (DPP-4) inhibitors allowed the safety of the T2DM therapy to be increased by reducing several parameters, including hypoglycaemia incidences, risks of cardiovascular complications and weight gain. Market approval of a new Russian drug in this group will ensure modern, efficient and affordable care for our patients.Aim.To study the efficacy and safety of a new DPP-4 inhibitor (gosogliptin) in comparison with that of vildagliptin as monotherapy as well as in combination with metformin in patients with T2DM who were not previously treated with drug therapy.Materials and methods.The study SRX-1374-02 involved 299 patients. In total, 149 patients were randomised to the gosogliptin group and 150 were randomised to the vildagliptin group. The groups were comparable with respect to baseline characteristics. In the first 12-week stage, patients received treatment with one of the study drugs as monotherapy. The decision was then made whether to continue the monotherapy regimen or to add metformin during the next 24 weeks. Dose titration of the study drugs and the addition of metformin were performed on the basis of glycaemia levels. The total treatment duration was 36 weeks.Results.After 12 weeks of monotherapy, НbА1с levels significantly decreased by -0.93% and -1.03% in the gosogliptin and vildagliptin groups, respectively. After the administration of combination therapy the decrease in НbА1с continued and was -1.29% in the gosogliptin + metformin group and -1.35% in the vildagliptin + metformin group when compared with baseline values. The difference in НbА1с reduction between the groups during both treatment periods was ≤0.1% (upper level of CI <0.4%), which led to the conclusion about the superior efficacy of gosogliptin over that of vildagliptin as monotherapy and in combination with metformin. By the end of the 36-week treatment period, НbА1с reached the target level of ≤7.0% in 56.4% and 55.4% of patients in the gosogliptin and vildagliptin groups, respectively (statistically significant differences between treatment groups were not found, p = 0.74).Conclusion.The results showed that gosogliptin is an effective hypoglycaemic agent from the group of DPP-4 inhibitors and can be recommended for use in patients with T2DM both as monotherapy and in combination with metformin.